Institutional image and missionary development as predictors of school satisfaction - Pereira Álvarez, Oscar Andrés (2021)
The variables institutional image and missionary fulfillment as predictors of student satisfaction are part of a correlational quantitative investigation, applied to 163 students from the 20 Adventist Educational Institutions of the South Colombian Union. The purpose is to know the correlation between student satisfaction as a recipient of the services of the Adventist educational system, and the variables of institutional image and missionary fulfillment, for the purposes of loyalty and retention of current students. A linear regression analysis was carried out by the method of successive steps, by which it was found that the variables, perception of the institutional image and perception of missionary fulfillment explain 47.9% the variance of student satisfaction.